Development of Learning Materials Making Virtual Learning-Based Videos Community Local Wisdom Through Learning Experience for Students - Zulkarnain Zulkarnain; Kukuh Miroso Raharjo (Faculty of Education Universitas Negeri Malang, 2021)
Abstract: The effectiveness of learning through virtual media is increasingly achieving its goals if lecturers and students can develop instructional video media as virtual learning materials. The use of instructional videos in the learning process needs to be systematically designed so that learning media can be used effectively, experience learning-based learning videos so that they are more contextual about the local wisdom of the community. The research objective was to produce a learning model and learning materials for the development of virtual learning video media based on local wisdom of the community through learning experience for students of the Department Non-Formal Education, Faculty of Education, State University of Malang. The research method used is the development (research development) development research model is an attempt to develop and validate educational products. The research design is systematical as follows: (1) the stage of analyzing, (2) the writing stage, (3) the stage of expert assessment and revising, and (4) the stage of the limited trial of the readability of the contents of learning materials related to understanding the content. The conclusion is based on the data analysis of the results of the content assessment on the development of learning materials for making virtual learning video media based on local wisdom of the community through a learning experience in the subject of learning resources and learning media department non-formal educations obtained valid results.